2016
DOI: 10.5812/ircmj.24231
|View full text |Cite
|
Sign up to set email alerts
|

The Stigma of Reproductive Health Services Utilization by Unmarried Women

Abstract: Background:Fear of the stigma associated with reproductive health services has always been one of the reasons why youth and unmarried individuals avoid making use of such services. This stigma imposes a great deal of mental stress, fear, and depression on patients and causes delays in the diagnosis and treatment of their conditions.Objectives:This paper explores the concept of stigma in the context of the utilization of reproductive health services by unmarried women.Patients and Methods:This study is qualitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 24 publications
0
29
0
1
Order By: Relevance
“…The results of 59 published papers were synthesised. Thirty-eight studies were cross-sectional surveys , nineteen were qualitative studies [72][73][74][75][76][77][78][79][80][81][82][83][84][85][86][87][88][89][90], and two employed mixed methods design [91,92]. Table 1 shows The majority of studies were conducted in Iran and Turkey, which are the fastest growing medical research output in the Middle East [93].…”
Section: Study Design and Sample Characteristicsmentioning
confidence: 99%
See 4 more Smart Citations
“…The results of 59 published papers were synthesised. Thirty-eight studies were cross-sectional surveys , nineteen were qualitative studies [72][73][74][75][76][77][78][79][80][81][82][83][84][85][86][87][88][89][90], and two employed mixed methods design [91,92]. Table 1 shows The majority of studies were conducted in Iran and Turkey, which are the fastest growing medical research output in the Middle East [93].…”
Section: Study Design and Sample Characteristicsmentioning
confidence: 99%
“…Findings suggested that mothers' attitudes towards SRH education affected young girls' access to information and education [77][78][79]. Many mothers wanted their daughters to learn but felt that they had inadequate information to give them, and others were embarrassed discussing such matters with their daughters [70,78].…”
Section: Theme 3: Barriers To Sexual and Reproductive Health Educatiomentioning
confidence: 99%
See 3 more Smart Citations